Assessment of the antinociceptive and anti-inflammatory activities of the stem methanol extract of Diplotropis purpurea - Lorena A. Cruz; Miguel A. Díaz; Mahabir P. Gupta; José Luis López-Pérez; Eily Mondolis; Juan Morán-Pinzón; Estela Guerrero (Taylor & Francis Group, 2019)
Context: Since there is still a great need to search for plant species with antinociceptive and anti-inflammatory activities, Diploptropis purpurea (Rich.) Amshoff (Fabaceae) is studied for the first time. Objective: This evaluates the analgesic and anti-inflammatory activities of the stem methanol extract of Diplotropis purpurea (MEDP). Material and methods: The anti-inflammatory and analgesic effects of MEDP of D. purpurea were evaluated in vivo. The antinociceptive activity was assessed in CD1 male mice were treated by oral gavage with 500 mg/kg of MEDP 30 min before submitting to acetic acid-induced abdominal writhing, hot-plate, and formalin tests. Paws oedema induced by carrageenan, histamine or serotonin were performed in male Sprague-Dawley rats to determinate the anti-inflammatory activity. Results: Oral administration of MEDP produced significant antinociceptive effects on the inflammatory phase in the formalin test [12.0 s versus 72.5 s in carboxymethyl cellulose (CMC) control group]. MEDP produced an analgesic effect in the hot-plate model, although the effect was modest compared to tramadol (40 and 60%, respectively). The oral administration of MEDP in a dose of 500 mg/kg showed maximum inhibition (75.1%) after 0.5 h in carrageenan-induced oedema, but it did not modify histamine or serotonin-induced oedemas. Discussion and conclusion: In the peripheral nociception model, acetic acid-induced abdominal writhing, the MEDP did not show a protective effect, but its analgesic effects were evident in the inflammatory phase of the formalin test and in the hot-plate model. These results show that the anti-inflammatory effect was accompanied by a reduction in the perception of painful stimuli.